2018
DOI: 10.1212/wnl.0000000000005560
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and prognostic value of CNS MOG autoimmunity in adults

Abstract: In adults, MOG-Ab-associated disease extends beyond clinical and radiologic abnormalities in the optic nerve and spinal cord. Despite the relapsing course, the overall visual and motor outcome is better compared with AQP4-Ab-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

44
540
10
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(641 citation statements)
references
References 37 publications
44
540
10
13
Order By: Relevance
“…Typically, lesions appear as a small number (≤3) of poorly demarcated infratentorial lesions, 103 and thalamic and pontine lesions are distinctive MRI findings. 104 Supratentorial deep white matter lesions can be seen (Fig. 17).…”
Section: Brain Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, lesions appear as a small number (≤3) of poorly demarcated infratentorial lesions, 103 and thalamic and pontine lesions are distinctive MRI findings. 104 Supratentorial deep white matter lesions can be seen (Fig. 17).…”
Section: Brain Lesionsmentioning
confidence: 99%
“…18). 104 Ogawa, et al 105 reported cases presenting with unilateral cortical encephalitis with epileptic seizure. Wang et al 106 reported that 21% of MOG-IgG-positive patients presented with encephalitis, and one-third of these patients also showed anti-N-methyl d-aspartase receptor antibody.…”
Section: Brain Lesionsmentioning
confidence: 99%
“…Recently, Marignier et al . reported that among 49 adult anti‐MOG antibody‐positive patients with abnormal brain MRI findings, infratentorial lesions were located in the midbrain (10.2%), pons (34.69%), medulla oblongata (14.29%), cerebellar peduncles (18.37%) and cerebellum (4.08%), as well as adjacent to the fourth ventricle (22.45%) …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Marignier et al reported that among 49 adult anti-MOG antibody-positive patients with abnormal brain MRI findings, infratentorial lesions were located in the midbrain (10.2%), pons (34.69%), medulla oblongata (14.29%), cerebellar peduncles (18.37%) and cerebellum (4.08%), as well as adjacent to the fourth ventricle (22.45%). 5 Therefore, lesions adjacent to the fourth ventricle that can involve cerebellar dentate nucleus might be one of the characteristic phenotypes of anti-MOG antibody-associated encephalitis. Further analysis is required to clarify the underlying pathophysiology and the clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…There is variable support in the literature for the relevance of persistent MOG antibody status for predicting recurrent disease . However, prevention of recurrence in the face of repeated neuroinflammatory events prevent future disability.…”
mentioning
confidence: 99%